The effect of mental workload on the intensity and emotional dynamics of perceived exertion - Cárdenas-Vélez, David; Perales, José C.; Chirosa, Luis J.; Conde-González, José; Aguilar-Martínez, Daniel; Araya, Sergio (Anales de Psicología / Annals of Psychology, 2013)
Perceived exertion, as measured by psychometric scales, has been proven to be a valid tool to assess training load, and to highly correlate with physiological and mechanical dimensions of physical effort. However, little is known about the emotional correlates of exertion, and how perceived exertion is influenced by mental workload. In the two experiments reported here, ratings of perceived exertion (RPE) were found to be significantly influenced by mental workload (generated by means of a cognitive task, unrelated to, but temporally overlapping with the physical task) during active recovery after exhausting exercise, but not during incremental exercise. Importantly, perceived exertion was found to strongly correlate with reported emotional/hedonic valence, but not so tightly with reported arousal. These findings strengthen the motivational value of perceived exertion, and its linkage to other psychological constructs